Struktur Vertikal Gelombang Planeter Di Mesosfer Ekuator Dari Pengamatan MF Radar Pontianak (0.03o LU - 109.3o BT) - Dyah RM; Buldan M (Indonesian Journal of Physics, 2003)
Atmospheric waves play a crucial role in atmospheric dynamics. Mechanism of generating, propagating, and breaking of waves are interesting to study, mainly in equator region, cause results of observation in the mid-latitude indicated equator region as global atmospheric dynamo. Data from Medium Frequency (MF) Radar at Pontianak at the height of 78 – 98 km in 1996 used to obtain vertical structure of variation of planetary waves from zonal and meridional winds in the mesosphere. Generally, intensity of variation of zonal winds higher than meridional. Variation of waves related to sun would be discuss. Variation of planetary waves related to sun over Pontianak didn’t show certain pattern. Results of observation at middle and higher latitude shown certain pattern of variation of planetary waves related to sun.